MEASUREMENT OF TECHNICAL EFFICIENCY DISPARITY OF COCOA PRODUCTION BY CERTIFICATION STATUS IN OGUN STATE, NIGERIA - Akinrinmola, F.K.; Ogunwande, I.O.; Esan, M.O. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study Compared the technical efficiency disparity of cocoa Production by certification status among farmers in Ogun State, Nigeria. A multistage sampling technique was used in selecting 240 respondents from the study area. Data were collected through the administration of well-structured questionnaire and analysed using descriptive statistics, stochastic frontier analysis, and probit regression model. The results revealed that cocoa farming is dominated by middle-aged to older men (51years and 53years), with majority (87% and 77%) respondents married and having more than 40years of farming experience (about 21 years and 25years). Majority (38.3% and 28.3%) of Certified farmers attained primary education and tertiary education respectively while 25.0% and 21.7% of non-certified farmers had primary and tertiary education. Most (89.2%) of the certified farmers had contact with extension agents while majority (51.7%) of the non-certified farmers had no contact with extension agents and achieved greater productivity (643.50kg/ha) compared to non-certified farmers (496.02kg/ha), despite non-certified farmers having larger average farm sizes (3.32ha) and slightly higher incomes (₦821,524.16). Stochastic frontier estimates indicated higher mean technical efficiency among certified farmers (0.678) relative to non-certified farmers (0.623), underscoring the role of certification in enhancing resource use and productivity. Ordinary Least Square regression results showed that age (0.086; p<0.01), gender(0.314; p<0.05), household size(0.092; p<0.10), farming experience (0.021; p<0.01), extension contacts(1.512; p<0.05), and farm size (0.109; p<0.10) significantly influenced the certification status of cocoa farmers. The study concluded that certified cocoa farmers have higher technical efficiency compared to their non-certified counterparts in the study area. The study recommends strengthening extension services, expanding access to credit, and promoting farmer training on certification requirements to improve cocoa productivity and sustainability.